One step facile in-situ photochemical synthesis of hollow, doughnut-like ZnO nanoparticles and their alcohol vapor sensing properties - Kirtay, Hicret; Omur, Birsel Can; Ahindal, Ahmet; Arsu, Nergis (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Parameters such as the type of photoinitiator and UV exposure time are investigated in order to tailor the growth of ZnO nanostructures into a variety of dimensions and structures. Based on the type of photoinitiator, by means of specific photoreducing radicals, hollow, doughnut and spherical-shaped ZnO nanoparticles are prepared in one step. 2-Mercapto-thioxanthone (TX-SH), Thioxanthone (TX) and a-aminoketone (Irg-907) are employed as the photoinitiators in formulations of PEGMEA/PEGDA (Poly (ethylene glycol) methyl ether acrylate/Poly (ethylene glycol) diacrylate). TX-SH containing formulations lead to the formation of hollow, doughnut-like shaped ZnO nanocomposites at early or prolonged irradiation times. Aggregation is much more prominent when TX is added to the formulation. Addition of Ph-SH to the TX containing formulation reduced agglomeration. Rather small and well-distributed ZnO nanoparticles are obtained for formulations consisting of Irg-907. Here we report an easy and fast photochemical preparation technique for these unique structures. The conduction behavior of the novel doughnut-like ZnO nanocomposite under various types of alcohol vapor (ethanol, methanol, and propanol) concentrations between 100 and 500 ppm has been investigated. It was found that the presence of alcohol vapor leads to an increase in sensor current. The ZnO nanocomposite based sensor showed maximum sensitivity toward methanol vapor for all the concentrations investigated.
Keywords: ZnO nanoparticles; Doughnut-shaped nanoparticles; Photopolymerization; Alcohol vapor sensing; Thio-Thioxanthone; SILVER-EPOXY NANOCOMPOSITES; ZINC-OXIDE; CATIONIC-POLYMERIZATION; ASSISTED SYNTHESIS; OPTICAL-PROPERTIES; PERFORMANCE; FILMS; NANOSTRUCTURES; PHOTOINITIATOR; NANOCRYSTALS; Materials Science